Mineralogy of lunar meteorites, Yamato-82192 and -82193 with reference to breccias in a breccia - Takeda,Hiroshi; Mori,Hiroshi; Tagai,Tokuhei (1987)
P(論文) The mineralogy of pyroxene, olivine and plagioclase fragments, lithic clasts and glassy matrices of lunar meteorites, Yamato-82192 (Y-82192) and Yamato-82193 (Y-82193), has been studied by an electron microprobe and an analytical transmission electron microscope (TEM). The distribution of the chemical compositions of pyroxene grains in Y-82192 and -82193 bears a strong resemblance to one another and covers almost all known pyroxenes in nonmare pristine rocks. They are similar to those of a lunar regolith breccia 60019,but appear to be different from Y-791197 and ALHA81005 in that Y-82 lunar meteorites have significantly fewer pyroxenes with extremely high Fe content. The difference implies that Y-82192 and -82193 may contain a fewer Fe-rich mare basalt components. The presence of a breccia in a breccia in Y-82192 indicates complex impact histories in the region where this meteorite was derived. The texture of the matrix glass of Y-82192 in the TEM scale is different from that of ALHA81005. departmental bulletin paper